Optimization and synthesis of an 18F-labeled dopamine D3 receptor ligand using [18F]fluorophenylazocarboxylic tert-butylester - Nebel, Natascha; Maschauer, Simone; Hocke, Carsten; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (Journal of Labelled Compounds and Radiopharmaceuticals, 2016)
There is still no efficient fluorine-18-labeled dopamine D subtype selective receptor ligand for studies with positron emission tomography. We aim at improving the D selectivity and hydrophilicity of a candidate ligand by changing the substitution pattern to a 2,3-dichlorophenylpiperazine and hydroxylation of the butyl chain. The compound [F]3 exhibited D affinity of K = 3.6 nM, increased subtype selectivity (K(D/D) = 60), and low affinity to 5-HT and α receptors (K (5-HT/D) = 34; K (α/D) = 100). The two-step radiosynthesis was optimized for analog [F]4 by reducing the necessary concentration of the precursor amine (57 mM), which reacted with [F]fluorophenylazocarboxylic tert-butylester under basic conditions. The optimization of the base (Cs CO, 23 mM) and the adjustment of reaction temperature led to the radiochemical yield of 63% after 5 min at 35C. The optimized reaction conditions were transferred on to the synthesis of [F]3 with an overall non-decay corrected yield of 8-12% in a specific activity of 32-102 GBq/μmol after a total synthesis time of 30-35 min. This provides a D radioligand candidate with improved attributes concerning selectivity and radiosynthesis for further preclinical studies.
Keywords: dopamine D3 receptor; nucleophilic aromatic 18F-fluorination; phenylazocarboxylic esters; positron emission tomography